The root growth-regulating brevicompanine natural products modulate the plant circadian clock - De Montaigu, A; Oeljeklaus, J; Krahn, J; Suliman, M; Halder, V; De Ansorena, E; Nickel, S; Schlicht, M; Plíhal, O; Kubiasová, K; Radová, L; Kracher, B; et al. (American Chemical Society, 2017)
Plant growth regulating properties of brevicompanines (Brvs), natural products of the fungus Penicillium brevicompactum, have been known for several years, but further investigations into the molecular mechanism of their bioactivity have not been performed. Following chemical synthesis of brevicompanine derivatives, we studied their activity in the model plant Arabidopsis by a combination of plant growth assays, transcriptional profiling, and numerous additional bioassays. These studies demonstrated that brevicompanines cause transcriptional misregulation of core components of the circadian clock, whereas other biological read-outs were not affected. Brevicompanines thus represent promising chemical tools for investigating the regulation of the plant circadian clock. In addition, our study also illustrates the potential of an unbiased -omics-based characterization of bioactive compounds for identifying the often cryptic modes of action of small molecules.